A Stable Precursor for Bioorthogonally Removable 3-Isocyanopropyloxycarbonyl (ICPrc) Protecting Groups - Tu, Julian; Xu, Minghao; Franzini, Raphael M. (Synlett, 2020)
Studies have established 3-isocyanopropyloxycarbonyl (ICPrc) moieties as bioorthogonally removable protecting groups. However, reagents to prepare ICPrc-protected amines are unstable, which critically limits the practical implementation of this chemistry. Here we report 3-isocyanopropyl (pentafluorophenyl) carbonates as bench-stable precursors for the synthesis of ICPrc-protected primary and secondary amines. The utility of the chemistry for bioconjugation applications is demonstrated by reversibly masking a lysine residue on a bioactive peptide.
Keywords: bioorthogonal; isonitrile; isocyanide; protecting groups; tetrazine